2002
DOI: 10.1182/blood.v100.2.594
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for the treatment of acute myelogenous leukemia based on folate receptor β–targeted liposomal doxorubicin combined with receptor induction using all-trans retinoic acid

Abstract: Up-regulation of folate receptor (FR) type-␤ in acute myelogenous leukemia (AML) by all-trans retinoic acid (ATRA) and its restricted normal tissue distribution makes it a potential target for therapeutic intervention. The FR-␤ in peripheral blood granulocytes was unable to bind folate and appeared to have a variant GPI membrane anchor, evident from its insensitivity to phosphatidylinositol-specific phospholipase C but not nitrous acid. Granulocyte FR-␤ lacked mutations, and neither deglycosylation nor deterge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
149
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(152 citation statements)
references
References 47 publications
3
149
0
Order By: Relevance
“…Liposomes were prepared by thin film hydration followed by polycarbonate membrane extrusion, as described previously (Haran et al, 1993;Pan et al, 2002). DOX was remoteloaded into the liposomes by a transmembrane pH gradient.…”
Section: Liposome Preparationmentioning
confidence: 99%
“…Liposomes were prepared by thin film hydration followed by polycarbonate membrane extrusion, as described previously (Haran et al, 1993;Pan et al, 2002). DOX was remoteloaded into the liposomes by a transmembrane pH gradient.…”
Section: Liposome Preparationmentioning
confidence: 99%
“…In contrast, FR-b expression is much more restricted. It appears to be present in some normal cells of myeloid lineage but is highly expressed in myeloid but not lymphoid leukemias (Shen et al, 1994;Reddy et al, 1999;Ross et al, 1999b;Pan et al, 2002). FR-b may have little function in normal myeloid progenitor cells, since receptors on these cells do not appear to bind or transport folate, possibly due to a defect in the GPI membrane anchor (Reddy et al, 1999;Pan et al, 2002).…”
Section: Folic Acid Receptor-mediated Transportmentioning
confidence: 99%
“…2 We have previously reported that the expression of FRb is limited to the myelomonocytic lineage and that its expression is increased during neutrophil maturation and during the activation of macrophage; 3,4 however, among normal hematopoietic cells, only the receptor expressed in activated macrophage is functional in having the ability to bind folate. 4,5 FRb is also expressed in a functional form in approximately 70% of acute myelogenous leukemia (AML) in which it is frequently coexpressed with CD34. 6 These observations suggest that FRb is a potential target for drug delivery to AML cells, but prospects of its clinical utility are limited by the variable and the frequently low expression of the receptor in the leukemic cells of AML patients.…”
mentioning
confidence: 99%
“…6 Our previous in vitro studies in both AML cell lines and primary AML cells have demonstrated that all-trans retinoic acid (ATRA) acts directly on the FRb gene to selectively upregulate its expression 6,7 and that this effect is potentiated by innocuous histone deacetylase (HDAC) inhibitors, including valproic acid (VPA). 8 The receptor induction sensitized AML cells to FRtargeted drugs including folate-coated liposomal doxorubicin 5 and the antifolate, dideazatetrahydrofolate. 8 Treatment with ATRA also increased the survival of mice that were injected KG1 AML cells in their peritoneal cavity upon treatment with FR-targeted liposomal doxorubicin.…”
mentioning
confidence: 99%
See 1 more Smart Citation